Improved biomonitoring of airborne contaminants by combined use of holm oak leaves and epiphytic moss - De Nicola, F.; Spagnuolo, V.; Baldantoni, D.; Sessa, L.; Alfani, A.; Bargagli, R.; Monaci, F.; Terracciano, S.; Giordano, S. (CHEMOSPHERE, 2013)
Concentrations of 12 elements (Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb and Zn) and 16 EPA-listed PAHs were detected in Quercus ilex leaves and the epiphytic moss Leptodon smithii collected at urban, periurban and extraurban holm oak stands, in two Italian Regions (Campania and Tuscany). Levels of environmental contaminants were generally higher in leaves and moss from urban areas than periurban and extraurban ones and samples from Campania had the highest PAH content. The epiphytic moss accumulated higher concentrations of trace elements than leaves and the latter showed a higher accumulation capability for PAHs, especially for those with low molecular weight. The different bioaccumulation in leaves and moss were explained in terms of their distinctive morphological and ecophysiological characteristics. The combined approach seems a promising tool for the monitoring of a wide range of pollutants in Mediterranean urban and extraurban environments. (C) 2013 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: Air pollution gradient; Bioaccumulation; Leptodon smithii; PAHs; Quercus ilex; Trace Elements

Trace metals, peroxidase activity, PAHs contents and ecophysiological changes in Quercus ilex leaves in the urban area of Caserta (Italy). - Papa, S; Bartoli, G; Nacca, F; D'Abrosca, B; Cembrola, E; Pellegrino, a; Fiorentino, a; Fuggi, A; Fioretto, a (Journal of environmental management, 2012)
Trace metals and polycyclic aromatic hydrocarbons, severely affecting human, animal and plants health, highly contribute to the air pollution in urban areas mainly due to car traffic. In this study the air biomonitoring of the city of Caserta (South Italy) has been performed by using Quercus ilex L., a widespread ornamental plant in parks, gardens and avenues. The plant leaves from different sites within the urban area were collected and used to determine the concentrations of V, Cd, Cr, Pb, Ni, Cu, and PAHs as well as the free amino acid content and peroxidase enzyme activity as indices of the leaf physiological conditions. All the tested trace metals showed concentrations higher than the control site. Lead was positively correlated to Cd and Cr and showed, also, a positive trend with Ni and Cu that, in their turn, were highly correlated between them. Positive and significant correlations were evidenced between total PAHs and carcinogenic PAHs and negative correlations between those and all trace metals assayed except V. Cu and Cd contents evidence negative correlations with peroxidase activity, and the free amino acid contents. The PAHs, in particular Carc-PAHs, were negatively correlated to the tested heavy metals. POD was positively correlated only with V and negatively correlated with Cu and Cd.
Keywords: Amino acid contents; PAHs; peroxidase; Quercus ilex leaves; Trace Elements; Urban area

Nutrients and trace elements content of wood decay fungi isolated from oak (Quercus ilex). - Campos, Juan a (Biological trace element research, 2011)
The presence of chemical elements and the differences in their concentration in the fruiting bodies of wood decay fungi may reflect their activity either as saprobes or parasites and the intimate physiological relation with the substrate from which they extract their nutrients. In order to test this hypothesis, we carried out a systematic sampling of eight species of wood decay fungi on oak (Quercus ilex). The data show that the concentration of some elements exhibits a very wide range of values for the species tested, which could mean that the relative content of some elements may provide clues about the nature of the substrate and, moreover, about the nutritional physiology. The comparison between the foliar analysis (FA) and the elemental content of fungi may shed light on the specific physiological behaviour of the species. Potassium is an element accumulated in fungal biomass in higher quantities than in the FA. By contrast, calcium appears in foliar analysis in much higher quantities than in fungal fruiting bodies' biomass. Concerning this element, we have also found profound differences between the two species phylogenetic groups and lifestyle. Of all elements measured, we believe that the relative accumulation of K and Ca may be related to the close connection between fungi and the substrate on which they live and may also explain their physiological role as saprobes or parasites. When the lifestyle and the systematic position of the different species sampled were compared, differences also emerged in the content of Na and Ca.
The following values have no corresponding Zotero field: accession-num: 21748305
Keywords: Epiphytic fungi; Heavy metals; Nutrients; Nutrition physiology; Saprobe fungi; Trace Elements

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Introduction of the factor of partitioning in the lithogenic enrichment factors of trace element bioaccumulation in plant tissues. - Sardans, Jordi; Penuelas, Josep (Environmental monitoring and assessment, 2006)
Bioindicators are widely used in the study of trace elements inputs into the environment and great efforts have been conducted to separate atmospheric from soil borne inputs on biomass accumulation. Many monitoring studies of trace element pollution take into account the dust particles located in the plant surface plus the contents of the plant tissues. However, it is usually only the trace element content in the plant tissues that is relevant on plant health. Enrichment factor equations take into account the trace element enrichment of biomasses with respect soil or bedrocks by comparing the ratios of the trace element in question to a lithogenic element, usually Al. However, the enrichment equations currently in use are inadequate because they do not take into account the fact that Al (or whichever reference element) and the element in question may have different solubility-absorption-retention levels depending on the rock and soil types involved. This constrain will become critical when results from different sites are compared and so in this article we propose that the solubility factors of each element are taken into account in order to overcome this constrain. We analysed Sb, Co, Ni, Cr, Pb, Cd, Mn, V, Zn, Cu, As, Hg, and Al concentration in different zones of Catalonia (NE Spain) using the evergreen oak Quercus ilex and the moss Hypnum cupressiforme as target species. We compared the results obtained in rural and non industrial areas with those from the Barcelona Metropolitan Area. We observed differences in Al concentrations of soils and bedrocks at each different site, together with the differences in solubility between Al and the element in question, and a weak correlation between total soil content and water extract content through different sites for most trace elements. All these findings show the unsuitability of the current enrichment factors for calculating lithospheric and atmospheric contributions to trace element concentrations in biomass tissues. The trace element enrichment factors were calculated by subtracting the part predicted by substrate composition (deduced from water extracts from soils and bedrock) from total concentrations. Results showed that for most of the trace elements analysed, trace elements enrichment factors were higher inside the Barcelona Metropolitan Area than outside, a finding that indicates that greater atmospheric inputs occur in urban areas. The results show that the most useful and correct way of establishing a reference for lithospheric and atmospheric inputs into the plant tissues is, first, to analyse samples of the same plant species collected from a number of sites possessing similar environmental conditions (climate, vegetation type, soil type) and, second, to use this new enrichment factor obtained by subtracting from the total concentration in plant tissue the predicted contribution of soil or bedrock extracts instead of that of total soil or bedrock concentrations.
Keywords: biomass; Bryopsida; Bryopsida: chemistry; Bryopsida: growth & development; Environmental Monitoring; Environmental Monitoring: methods; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: growth & development; Quercus; Quercus: chemistry; Quercus: growth & development; Soil Pollutants; Soil Pollutants: analysis; Spain; Trace Elements; Trace Elements: analysis

Introduction of the factor of partitioning in the lithogenic enrichment factors of trace element bioaccumulation in plant tissues. - Sardans, Jordi; Penuelas, Josep (Environmental monitoring and assessment, 2006)
Bioindicators are widely used in the study of trace elements inputs into the environment and great efforts have been conducted to separate atmospheric from soil borne inputs on biomass accumulation. Many monitoring studies of trace element pollution take into account the dust particles located in the plant surface plus the contents of the plant tissues. However, it is usually only the trace element content in the plant tissues that is relevant on plant health. Enrichment factor equations take into account the trace element enrichment of biomasses with respect soil or bedrocks by comparing the ratios of the trace element in question to a lithogenic element, usually Al. However, the enrichment equations currently in use are inadequate because they do not take into account the fact that Al (or whichever reference element) and the element in question may have different solubility-absorption-retention levels depending on the rock and soil types involved. This constrain will become critical when results from different sites are compared and so in this article we propose that the solubility factors of each element are taken into account in order to overcome this constrain. We analysed Sb, Co, Ni, Cr, Pb, Cd, Mn, V, Zn, Cu, As, Hg, and Al concentration in different zones of Catalonia (NE Spain) using the evergreen oak Quercus ilex and the moss Hypnum cupressiforme as target species. We compared the results obtained in rural and non industrial areas with those from the Barcelona Metropolitan Area. We observed differences in Al concentrations of soils and bedrocks at each different site, together with the differences in solubility between Al and the element in question, and a weak correlation between total soil content and water extract content through different sites for most trace elements. All these findings show the unsuitability of the current enrichment factors for calculating lithospheric and atmospheric contributions to trace element concentrations in biomass tissues. The trace element enrichment factors were calculated by subtracting the part predicted by substrate composition (deduced from water extracts from soils and bedrock) from total concentrations. Results showed that for most of the trace elements analysed, trace elements enrichment factors were higher inside the Barcelona Metropolitan Area than outside, a finding that indicates that greater atmospheric inputs occur in urban areas. The results show that the most useful and correct way of establishing a reference for lithospheric and atmospheric inputs into the plant tissues is, first, to analyse samples of the same plant species collected from a number of sites possessing similar environmental conditions (climate, vegetation type, soil type) and, second, to use this new enrichment factor obtained by subtracting from the total concentration in plant tissue the predicted contribution of soil or bedrock extracts instead of that of total soil or bedrock concentrations.
The following values have no corresponding Zotero field: accession-num: 16648953
Keywords: biomass; Bryopsida; Bryopsida: chemistry; Bryopsida: growth & development; Environmental Monitoring; Environmental Monitoring: methods; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: growth & development; Quercus; Quercus: chemistry; Quercus: growth & development; Soil Pollutants; Soil Pollutants: analysis; Spain; Trace Elements; Trace Elements: analysis

Temporal and spatial variation in C, N, S and trace element contents in the leaves of Quercus ilex within the urban area of Naples. - Alfani, a; Baldantoni, D.; Maisto, G.; Bartoli, G.; Virzo De Santo, A. (Environmental pollution (Barking, Essex : 1987), 2000)
This paper presents a comparative analysis of the concentrations of C, N and S and several trace elements (Fe, Mn, Na, Zn, Cu, V, Pb, Ni, Cr, Cd) in leaves of Quercus ilex, an evergreen oak, collected in the urban area of Naples in 1989 and 1996. The samplings were carried out from 25 urban sites (roads with different traffic flows as well as urban and suburban parks) and from two remote areas as controls. Relative to 1989, the values measured in 1996 denote a strong decrement of S, Fe, Na, Pb, and Cr, with the exception of S in control sites. By contrast, C, N and Cd contents were higher in 1996 than in 1989. Cu and Ni showed a conspicuous increment in control sites as well as in urban sites facing the sea and in the parks, while in all the other urban sites these elements decreased remarkably. No significant difference was found in the leaf contents of Mn, Zn and V measured in 1989 relative to 1996. Both in 1989 and 1996 the contents of N, S, Fe, Na, Cu, Pb, V, Ni, Cr and Cd were significantly higher in leaves from urban sites than in the controls, reflecting the high degree of contamination of the urban area. Concentration factors expressed as the ratio of road/control values for most of the elements were still very high in leaves collected in 1996, though remarkably lower than in 1989.
The following values have no corresponding Zotero field: accession-num: 15092919
Keywords: air pollution biomonitoring; leaf elemental analysis; no x; so 2; Trace Elements

Temporal and spatial variation in C, N, S and trace element contents in the leaves of Quercus ilex within the urban area of Naples. - Alfani, a; Baldantoni, D; Maisto, G; Bartoli, G; Virzo de Santo, A (Environmental pollution (Barking, Essex : 1987), 2000)
This paper presents a comparative analysis of the concentrations of C, N and S and several trace elements (Fe, Mn, Na, Zn, Cu, V, Pb, Ni, Cr, Cd) in leaves of Quercus ilex, an evergreen oak, collected in the urban area of Naples in 1989 and 1996. The samplings were carried out from 25 urban sites (roads with different traffic flows as well as urban and suburban parks) and from two remote areas as controls. Relative to 1989, the values measured in 1996 denote a strong decrement of S, Fe, Na, Pb, and Cr, with the exception of S in control sites. By contrast, C, N and Cd contents were higher in 1996 than in 1989. Cu and Ni showed a conspicuous increment in control sites as well as in urban sites facing the sea and in the parks, while in all the other urban sites these elements decreased remarkably. No significant difference was found in the leaf contents of Mn, Zn and V measured in 1989 relative to 1996. Both in 1989 and 1996 the contents of N, S, Fe, Na, Cu, Pb, V, Ni, Cr and Cd were significantly higher in leaves from urban sites than in the controls, reflecting the high degree of contamination of the urban area. Concentration factors expressed as the ratio of road/control values for most of the elements were still very high in leaves collected in 1996, though remarkably lower than in 1989.
Keywords: air pollution biomonitoring; leaf elemental analysis; no x; so 2; Trace Elements

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G; Rutigliano, F a; Maisto, G; De Santo, a V (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Characterization of mineral content in Quercus ilex leaves by photon and neutron activation analysis - Bruno, Franco; Capannesi, Geraldo; Gratani, Loretta; Manes, Fausto (Giornale botanico italiano, 1980)
Abstract As part of a research on the holm oak stand and the Mediterranean « macchia » of Castelporziano, this study has provided the mineral characterization of Quercus ilex leaves by means of photon and neutron activation analysis. Although there is no evidence to indicate a selective distribution of the elements in the trees' crowns, some correlations are of considerable interest. Highly significant correlation coefficients are observed for the following pairs of elements: Fe-Sc, Fe-Cr, Fe-Th, Fe-Eu.
doi: 10.1080/11263508009427960
Keywords: Castelporziano (voyant); leaves and twigs; nuclear analysis; Quercus ilex; Trace Elements